1984
DOI: 10.1098/rstb.1984.0064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidic desposition on forest soil and vegetation

Abstract: The paper concerns the potential effects of acidic deposition on the nutrient status of soil and forest and on the possible toxic effect of increased Al solubility. The nutrient status of trees may be influenced by pollutants interacting with the foliage and also by changing availability of nutrients in the soil. N compounds are often absorbed by the canopy whereas base cations are lost to the soil by foliar leaching. Cation leaching increases with increased acidity of precipitation. Throughfall acidity varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 7 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…On the other hand, different authors reported variable responses of root growth of one species (Picea abies) to similar concentrations of Al (e.g. Rost-Siebert, 1983;Abrahamsen, 1984;Ingestad et al, 1985).…”
Section: Acidic Depositionmentioning
confidence: 99%
“…On the other hand, different authors reported variable responses of root growth of one species (Picea abies) to similar concentrations of Al (e.g. Rost-Siebert, 1983;Abrahamsen, 1984;Ingestad et al, 1985).…”
Section: Acidic Depositionmentioning
confidence: 99%
“…Evans, 1984;Jacobson et al, 1990;Back, Neuvonen & Huttunen, 1994). For example, long-term detrimental effects of acid deposition on plant growth have been reported, especially when sulphuric acid is applied and when rain has been allowed to reach the soil (Leith et al, 1989;Jacobson et al, 1990;Back et al, 1994), with a likely delayed negative growth response to acid application (Abrahamsen, 1984;Back et al, 1994). On the other hand, enhanced tree \igour and increased biomass growth observed, for instance, in Scandinavian trees (Kenttamies, 1991) are usually related to a possible fertilizing effect of nitrogen deposition during the earlier stages of acidification (Wood & Bormann, H 7;Kauppi, Mielikainen & Kuusela, 1992).…”
Section: Introduction Scandinavian Ecosystems Thus Over 80 °O Of Thementioning
confidence: 99%
“…Little is known about the effects of acid rain on ground vegetation in boreal forests (Abrahamsen, 1984;Hutchinson, Dixon & Scott, 1986;Hutchinson et al, 1987;Hutchinson & Scott, 1988;Nygaard & Abrahamsen, 1991). However, it has been suggested that the dynamics of ground vegetation, especially of certain ericaceous understorey shrubs and the lichen-moss bottom layer, inter alia maintain the success of tree regeneration in northern forests (Mallik, 1995;Zacknsson et al, 1995) and are therefore of particular importance when considering long-term effects of acid precipitation on these ecosystems.…”
Section: Introduction Scandinavian Ecosystems Thus Over 80 °O Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…During the last fifteen years soil acidification processes have attracted increased interest due to consequences of industrial pollution over forested areas, especially in North and Central Europe (Tamm, 1976;Abrahamsen, 1984;Van Breemen, 1985;Kauppi et al, 1986;Wittig, 1986;FalkengrenGrerup, 1986FalkengrenGrerup, , 1987Hallbäcken and Tamm, 1986;Tyler, 1987). Acidification markedly affects the area near the trunk base of trees, as has been assessed by soil pH and vegetation data (Zinke, 1962;Lane and Witcher, 1963;Wittig and Neite, 1985;Cloutier, 1985;Riha et al, 1986a,b;Wittig, 1986) and study of the mycorrhizal types (Kumpfer and Heyser, 1986).…”
Section: Introductionmentioning
confidence: 99%